Ancient civilizations - Clapham, Frances M.; Fagg, Christopher; Chamberlain, Nigel (New York : Warwick Press, 1978)
Discusses civilizations of the ancient world, including Mesopotamia, Egypt, Greece, Persia, Phoenicia, Rome, India, and China.
Includes bibliographical references and index.
Keywords: Civilization, Ancient; Civilization, Ancient